Legal Protection for Online Taxi Drivers Against Unilateral Cancellation of Orders by Passengers from a Maqasid Syariah Perspective - Atiya Aqilata Halawiyah; Ardiansyah (LP2M IAIN Palopo, 2026)
Online transportation services facilitate public mobility, but passengers often unilaterally cancel orders after the driver has accepted and is on their way to the pickup location, or even after arriving at the pickup point. This situation results in losses for drivers, while compensation mechanisms are limited and lack transparency. This study aims to analyze legal protection for drivers and examine this practice from a maqā (lawful) perspective.ṣid al-syarī'Ah, specificallyḥifẓal-malThe method used is empirical legal research with a qualitative approach through interviews and literature review. The results show that protection for online taxi drivers is still partial and does not yet have a uniform standard. From the perspective of maqāṣid al-syarī'AhThis practice contradicts the principle of asset protection because it results in losses without equitable compensation. Therefore, a fairer and more transparent compensation policy is needed to protect drivers